Bacterial strategies along nutrient and time gradients, revealed by metagenomic analysis of laboratory microcosms - Song, Ho-Kyung; Song, Woojin; Kim, Mincheol; Tripathi, Binu M.; Kim, Hyoki; Adams, Jonathan M. (Oxford University Press, 2017)
There is considerable interest in the functional basis of ecological strategies amongst bacteria. We used laboratory microcosms based on culturing of elutant from soil, to study the effects of varying initial nutrient concentration, and time succession, on the community metagenome. We found a distinct set of nutrient related or time related changes in the functional metagenome. For example a high nutrient (copiotrophic) strategy was associated with greater abundance of genes related to cell division and cell cycle, while a low nutrient (oligotrophic) strategy had greater abundance of genes related to carbohydrate metabolism and virulence, disease and defense. We also found time related changes in the functional metagenome, revealing a distinct ‘r’ related strategy with greater abundance of genes related to regulation and cell signaling, and a ‘K’ strategy rich in motility and chemotaxis related genes. These different gene-based strategies may help to explain how so many bacterial OTUs coexist in nature, and the functional principles dominating natural communities. In terms of diversity, both the OTU richness and the richness of species assignment of functional genes showed linear correlations with functional gene richness, supporting the hypothesis that greater taxonomic diversity is associated with greater functional diversity, with possible implications for ecosystem stability.
Keywords: Metagenome; Ecological strategy; Ecological succession; r/K-strategy; Copiotrophy; Oligotrophy